Hubungan Indeks Massa Tubuh dengan Kadar Glukosa Darah Sewaktu pada Mahasiswa Teknologi Laboratorium Medis Program Diploma Tiga STIKES Wira Medika Bali - Anjaswari, Ni Made Dian; Abadi, Moh. Fairuz; Prasetya, Didik (Poltekkes Kemenkes Semarang, 2025)
Body Mass Index (BMI) is a simple parameter used to assess a person's nutritional status, whether they are underweight or overweight. Overweight is often associated with the risk of elevated blood glucose levels (hyperglycemia), which can develop into metabolic syndrome. This condition is increasingly found in adolescents and young adults with unhealthy lifestyles. Therefore, this study was conducted to determine the relationship between BMI and random blood glucose levels (RBG) in regular students of the Diploma III Medical Laboratory Technology program at Wira Medika Bali Health College. This study employed an observational analytical method with a cross-sectional approach. A sample of 30 students was selected through purposive sampling based on inclusion criteria: aged 15–24 years, not taking medications that affect blood sugar levels, and willing to participate. BMI data were obtained through weight and height measurements, then categorized into underweight, normal weight, overweight, obesity I, and obesity II. RBG examinations were performed using capillary blood with the aid of a glucometer. Analysis of the relationship between variables used the Spearman Rank Test. The results showed that the BMI distribution of respondents was 13.3% underweight, 40.0% normal weight, 13.3% overweight, 23.4% obesity I, and 10.0% obesity II. All respondents had random blood glucose levels <200 mg/dL, thus remaining within the normal range. Statistical testing showed a p-value of 0.996 (p>0.05), concluding that there was no significant relationship between BMI and GDS in students. The conclusion of this study is that BMI has not been proven to be directly related to random blood glucose levels. However, weight control remains necessary as a long-term preventive measure against metabolic syndrome and other non-communicable diseases associated with obesity.